The care for the mother tongue in mediaeval Iceland and beyond - tarsi, matteo (FÉLAGSVÍSINDASTOFNUN HÁSKÓLA ÍSLANDS, 2016)
This article examines the care for the mother tongue in the Middle Ages. The starting point of this discussion is given by a Festschrift article by Sverrir Tómasson (Málvöndun á miðöldum, 1998). In the present article more examples are given of the care for the mother tongue in mediaeval Iceland. Moreover, the phenomenon is put into a wider cultural frame, namely that of the Western European Middle Ages. Examples of the care for the mother tongue are given both from the Germanic world (England, Germany and Denmark) and the Romance world (Italy). The main tenet of this article is that the care for the mother tongue, seen as a process of acquisition and adaptation of foreign concepts to a language/culture, is strongly tied, for what concerns the Middle Ages, to the importance and wealth of the written tradition in Latin against that in the vernacular.